Molecular Diagnosis of Mycoplasma pneumoniae in Synovial Fluid of Rheumatoid Arthritis Patients - Reza Golmohammadi; Ramezan Ali Ataee; Gholam Hossein Alishiri; Reza Mirnejad; Ali Najafi; Mehdi Tate; Davoude Esmaieli; Nematollah Jonaidi Jafari (Iranian Journal of Medical Microbiology, 2014)
Background and Aim: The role of Mycoplasma super antigens in inflammatory diseases such as rheumatoid arthritis (RA) is taken into consideration. Therefore, the aim of this study was to diagnosis of Mycoplasma pneumoniae in synovial fluid (SF) of patients with RA.Materials and Methods: In this study, 131 synovial fluid samples of patients with RA were collected during 3 years (2011- 2013). Mycoplasma pneumoniae ATCC: 29342 strain was used as control. The genome of samples is extracted separately and PCR protocol by M. pneumoniae species and mycoplasma genus identifier primers was carried out. The PCR product was confirmed by sequencing. Results: The results of this study showed that this molecular diagnosis method is able to detect M. pneumoniae in the synovial fluid of patients with RA. So that M. pneumoniae species was confirmed in 30 samples (22.9%) and Mycoplasma genus detected in the 70 sample (53.4%). Conclusions: based on the results of this study, the PCR molecular method was able to detect of the Mycoplasma genus and also M. pneumoniae species in the synovial fluid of patients with RA. The results indicated that M. pneumoniae can be a probable cause of rheumatoid arthritis disease. This finding may help the specific treatment of RA.